(3GdJegjO aj JfRjd GdaQhY Ydi GdCUhds - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eRjd CYPGQ Gdecdajf HEQTGO GdYbhd hHYO aEf CUhd Gdabg Yde YXe faYg hbOQg hbO egOJ HcJGHi gPG WQjb GdJNQjL dcd Pi ePgH haJMJ Hg HGH GdJaQjY dcd Pi eWdH s
(3BNQgG (B:s
(3ceG dh Mce dfaSg Ke JZjQ ELJgGOg JZjQkG dGjbJVi GdfbV Ke JQGaY Edjg ZQeGA GdhbGYI GdJi Mce ajgG aEfg jeVi Mceg GdChd hEf COi ELJgGOg Edi Cf ZjQg CUhH ceG PcQg GdQGaYi ai cJGH GdbVGA , hGddg CYde s
(3GdfSNI HgG MhGTs
(3Hg eWGdH ddcJGHs
(3HBNQg JQLeI ddeDda efbhdg HJUQa Yf cJGH MSf GdeMGVQI ddSjhWis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs